Yoga as a complex intervention and its development for health-related quality of life in adult cancer - McCall MacBain, M (2015)
The aim of this thesis was to develop yoga as a complex intervention in health care for the improvement of health-related quality of life (HRQoL) in adult cancer. As the Indian tradition of practising yoga increases in popularity worldwide, populations in the West are beginning to see yoga as an opportunity to prevent and treat health conditions. The Medical Research Council’s framework has provided a methodology to address a paucity of coherent evidence for the myriad of unsupported health claims made by yoga enthusiasts. The thesis structure included a step-by-step approach to investigate biomedical theories of how yoga might work to improve health, to synthesise evidence of yoga interventions, to model their process and outcomes, and to test evaluation procedures in the context of a randomised controlled trial (RCT). The results of a bibliometric analysis indicated an overall increase in the publication rate of yoga research in health care, and in 2005 this research began to focus on cancer. A component analysis, semi-structured patient interviews (n=10) and oncologist surveys (n=29) were successively designed, implemented and analysed to advance a model of yoga intervention specific to adult cancer. The cumulative results were applied to design three yoga interventions randomly allocated to men and women receiving treatment for cancer (n=15). Outcomes of the feasibility study demonstrated that yoga intervention is appropriate for adult patients and can be administered safely in a clinical setting. In its conclusion, this thesis produces evidence-based support for the optimisation of yoga intervention in the context of a large-scale RCT for HRQoL in adult cancer, and it provides recommendations to improve research methodology and reporting of complex interventions in health care.